Determining of Soil-to-plant transfer factors of strontium ion from the soil sample of Tehran province to two plant species including radish and watercress and investigating the influencing parameters - M. Zavar Mousavi; S.A.H. Feghhi; H. Aghayan; A.M. Taherian; H. Ghasemi Mobtaker; T. Yousefi (مجله علوم و فنون هسته‌ای, 2023)
This research investigates the transfer factor in the soil to plant (as one of the important parameters in safety analysis calculations and determining the amount of radiation of people) of strontium ion (a conventional radionuclide in pollution caused by nuclear accidents) to two plant samples including radish (Raphanus sativus var. sativus) and watercress (Lepidium sativum) as highly consumed plants in the food chain grown in the southern soil of Tehran. In this research, experiments were carried out in pots with a diameter of 15.5 cm and a height of 15.7 cm. These pots contained 2 kg of soil mixed with compost under the natural sunlight conditions of Tehran. In order to investigate the effect of strontium ion concentration on the transfer factor, the desired soil was first mixed with compost at a ratio of 3:1 and, using strontium nitrate salt solution in four different concentrations (50-200-500-1000 mg/kg) was infected. Pots were irrigated weekly with a specific volume of water at two different acidity levels (pH = 5 and 6) to investigate the effect of pH on the transfer factor. Also, the concentration of strontium ions in two tissues of the leaf and root of radish and watercress was done. This was examined to determine the accumulation of strontium ions in each of the tissues and their influence on the transfer factor. The results showed that with the increase in soil strontium concentration, the amount of adsorption of this element in both plants increases and the transfer factor decreases. Also, the plant had more adsorption in the soil with lower pH and a higher transfer factor was reported. The comparison of transfer factor and strontium adsorbed between the two plants also showed that radish adsorbed more strontium than watercress and had more transfer factor. Also, using an experimental method, the distribution coefficient, which is a crucial and practical parameter in pollutant transfer modeling and pollution risk assessment in soil and water resources, was determined by using the transfer factor from soil to plant. In this research, the possibility of decontamination of strontium from the soil by applying radish was investigated. The results showed that this plant could be used as a purifier to purify soils contaminated with strontium.